2006
DOI: 10.1080/00207590500345401
|View full text |Cite
|
Sign up to set email alerts
|

A cross‐cultural study of environmental belief structures in USA, Japan, Mexico, and Peru

Abstract: Throughout history, the way in which people conceive nature/human relationships has dramatically changed, and different cultures also have divergent notions regarding the role humans play in nature. In Western societies a “new environmental paradigm” (NEP) of ecological nature has apparently replaced the old “human exception paradigm” (HEP), which conceives of humans as being superior and apart from nature. Previous research has shown that, in those societies, a marked dichotomy exist between these two apparen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
46
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(59 citation statements)
references
References 20 publications
9
46
0
4
Order By: Relevance
“…Analysis derived from such surveys often resorts to conjecture to explain the cultural roots of environmental values and is mostly mute on the question of how these values change in a multicultural context (Dietz, Fitzgerald, and Shwom 2005). Many studies see relatively fixed cultural traits, such as Chinese altruism or a Latino orientation toward the family, as the source of interethnic variation in environmental values (Cordell, Green, and Betz 2002;Bechtel et al 2006;Deng, Walker, and Swinnerton 2006). Rather than resort to such crude "essentialisms" (Robbins 2004, 198; see also Pulido 1998), we hope to show how environmental values are shaped by lived experience in place(s), which surely differ among ethnic groups but not because of differences in their basic character.…”
Section: Analysis Of Environmental Values Across Culturesmentioning
confidence: 99%
“…Analysis derived from such surveys often resorts to conjecture to explain the cultural roots of environmental values and is mostly mute on the question of how these values change in a multicultural context (Dietz, Fitzgerald, and Shwom 2005). Many studies see relatively fixed cultural traits, such as Chinese altruism or a Latino orientation toward the family, as the source of interethnic variation in environmental values (Cordell, Green, and Betz 2002;Bechtel et al 2006;Deng, Walker, and Swinnerton 2006). Rather than resort to such crude "essentialisms" (Robbins 2004, 198; see also Pulido 1998), we hope to show how environmental values are shaped by lived experience in place(s), which surely differ among ethnic groups but not because of differences in their basic character.…”
Section: Analysis Of Environmental Values Across Culturesmentioning
confidence: 99%
“…In these studies, negative correlations between ecocentric (NEP) and anthropocentric (HEP, Human Exemptionalism Paradigm) views in countries like Canada, Spain and the USA have been found, while positive correlations have been detected in countries like Brazil and Mexico, thereby suggesting that both dimensions, far from being opposed, may indeed be reconciled. For their part, Bechtel, Corral-Verdugo, Asai, and González--Riesle (2006) added an Asian culture to their study and looked into the structure of environmental beliefs in the USA, Mexico, Peru and Japan. They found that a dichotomic NEP-HEP structure was only corroborated among USA students.…”
mentioning
confidence: 99%
“…This tripart factor structure was then somewhat confirmed by Geller and Lasley (1985). Since that time, a number of studies have found that the NEP scale, in both the original and the revised versions, has two or more dimensions (e.g., Bechtel et al, 2006;Corral-Verdugo & Armendariz, 2000;Edgell & Nowell, 1989;Englis & Phillips, 2013;Fleury-Bahi et al, 2015;Furman, 1998;Gooch, 1995;Noe & Snow, 1990;Schuett & Ostergren, 2003;Woodworth et al, 2011).…”
Section: Introductionmentioning
confidence: 61%
“…For this reason, it is crucial to anticipate variation in the coherence of the NEP and study its causes. Several cross-national studies (e.g., Bechtel et al, 2006;Bechtel et al, 1999) use a comparative research design to demonstrate that cultural differences may influence the structure and belief constraint of the NEP. Similarly, Aoyagi-Usui et al (2003) and Heyd (2010) highlight the importance of examining cultural norms and traditions in terms of their impact on environmental values and beliefs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation